Pulsed Dye Laser-mediated Photodynamic Therapy is Less Effective than Conventional Photodynamic Therapy for Actinic Field Cancerization: A Randomized Half-side Comparative Study - Vivian Lindholm; Sari Pitkänen; Marika Schröder; Sonja Hahtola; Helka Sahi; Heini Halme; Kirsi Isoherranen (Medical Journals Sweden, 2021)
Previous research presents pulsed dye laser-mediated photodynamic therapy as a promising alternative to conventional red-light photodynamic therapy. In this study, 60 patients with 2 or more actinic keratoses randomly received either of these treatments on each side of the head. A physician blinded to the treatment evaluated treatment response at 6 months for each lesion, as completely, partially or not healed. Significantly lower complete clearance rates (10.3% vs 44.9%) and lesion-specific complete clearance rates were found for pulsed dye laser-mediated photodynamic therapy (47.9%) vs conventional red-light photodynamic therapy (73.4%). Significantly lower pain scores were found for pulsed dye laser-mediated photodynamic therapy, with a mean numerical rating of 2.3, compared with 4.1 for conventional red-light photodynamic therapy. The study population had a mean of 7.9 lesions, and 78% of patients had been treated previously for actinic keratoses on the treatment area. To conclude, in a population with severe sun damage, pulsed dye laser-mediated photodynamic therapy seems less effective than conventional red-light photodynamic therapy. Pulsed dye laser-mediated photodynamic therapy may still be a treatment option for patients who are not compliant with conventional red-light photodynamic therapy.